Follow up in shariah auditing: multiple approaches by takaful operators - Mohamad Puad, Noor Aimi; Abdullah, Nurdianawati Irwani; Shafii, Zurina (International Research Centre of Islamic Economics and Finance (IRCIEF), International Islamic University College Selangor (KUIS), 2020)
The growth of Islamic finance in Malaysia has been supported by strong financial institution structures and a robust regulatory framework. This include the function of shariah audit which has become mandatory since the issuance of Shariah Governance Framework in 2011 and it recently has been further enhanced in the Shariah Governance policy document 2019. The main objective of the shariah audit function is to provide independent evaluation and objective assurance designed to add value and improve Shariah compliance among Islamic Financial Institutions. To ensure the effectiveness of this function, the shariah audit process must be conducted comprehensively. However, the insufficiency of specific shariah audit guidelines becomes the challenge for auditors to conduct a comprehensive shariah audit procedure including the crucial final stage; follow up process. Therefore, the main objective of this study is to analyse the approaches of follow-up process which have been practised by Takaful Operators in Malaysia. A series of semi-structured interviews were undertaken with the auditors in Malaysian Takaful Operators who were involved directly in the shariah audit process. This study offers in-depth explanation on the follow-up process and provides recommendations on the characteristics of the best practice to be adopted for the follow-up process. The recommendations from the study are useful in enhancing the current shariah audit practices as well as improving the shariah audit quality.